Influence of the thickness of an antiferromagnetic IrMn layer on the static and dynamic magnetization of weakly coupled CoFeB/IrMn/CoFeB trilayers - Jhajhria, Deepika; Pandya, Dinesh K.; Chaudhary, Sujeet (Beilstein Journal of Nanotechnology, 2018)
The static and dynamic magnetization response of the CoFeB/IrMn/CoFeB trilayer system with varying thickness of the antiferromagnetic (AF) IrMn layer is investigated using magnetization hysteresis (M–H) and ferromagnetic resonance (FMR) measurements. The study shows that the two CoFeB layers are coupled via a long-range dynamic exchange effect through the IrMn layer up to a thickness of 6 nm. It is found that with the increase in IrMn layer thickness a nearly linear enhancement of the effective magnetic damping constant occurs, which is associated with the simultaneous influence of spin pumping and interlayer exchange coupling effects. An extrinsic contribution to the linewidth originating from the two-magnon scattering is also discussed. The AF-induced interfacial damping parameter is derived by studying the evolution of damping with inverse CoFeB thickness. The static magnetic measurements also reveal the interlayer exchange coupling across the IrMn layer both at room temperature and low temperature. The asymmetric hysteresis loop and training effect observed at low temperature is related to the presence of a metastable AF domain state. We show that both the static and dynamic magnetic properties of trilayer films can be adjusted over a wide range by changing the thickness of the IrMn spacer layer.
Keywords: ferromagnetic resonance; interlayer exchange coupling; magnetic damping; magnetic thin films; spin pumping

(untitled) - Nogués, J.; Schuller, I. K. (J. Magn. Magn. Mater., 1999)

(untitled) - Jungwirth, T.; Marti, X.; Wadley, P.; Wunderlich, J. (Nat. Nanotechnol., 2016)

(untitled) - Park, B. G.; Wunderlich, J.; Martí, X.; Holý, V.; Kurosaki, Y.; Yamada, M.; Yamamoto, H.; Nishide, A.; Hayakawa, J.; Takahashi, H.; Shick, A. B.; Jungwirth, T. (Nat. Mater., 2011)

(untitled) - Marti, X.; Fina, I.; Frontera, C.; Liu, J.; Wadley, P.; He, Q.; Paull, R. J.; Clarkson, J. D.; Kudrnovský, J.; Turek, I.; Kuneš, J.; Yi, D.; et al. (Nat. Mater., 2014)

(untitled) - Cheng, R.; Xiao, D.; Brataas, A. (Phys. Rev. Lett., 2016)

(untitled) - Železný, J.; Wadley, P.; Olejník, K.; Hoffmann, A.; Ohno, H. (Nat. Phys., 2018)

(untitled) - Wang, C.; Seinige, H.; Cao, G.; Zhou, J.-S.; Goodenough, J. B.; Tsoi, M. (Phys. Rev. X, 2014)

(untitled) - Mendes, J. B. S.; Cunha, R. O.; Alves Santos, O.; Ribeiro, P. R. T.; Machado, F. L. A.; Rodríguez-Suárez, R. L.; Azevedo, A.; Rezende, S. M. (Phys. Rev. B, 2014)

(untitled) - Wu, S. M.; Zhang, W.; KC, A.; Borisov, P.; Pearson, J. E.; Jiang, J. S.; Lederman, D.; Hoffmann, A.; Bhattacharya, A. (Phys. Rev. Lett., 2016)

(untitled) - Prakash, A.; Brangham, J.; Yang, F.; Heremans, J. P. (Phys. Rev. B, 2016)

(untitled) - Ralph, D. C.; Stiles, M. D. (J. Magn. Magn. Mater., 2008)

(untitled) - Núñez, A. S.; Duine, R. A.; Haney, P.; MacDonald, A. H. (Phys. Rev. B, 2006)

(untitled) - Gomonay, H. V.; Loktev, V. M. (Phys. Rev. B, 2010)

(untitled) - Swaving, A. C.; Duine, R. A. (Phys. Rev. B, 2011)

(untitled) - Wang, H.; Du, C.; Hammel, P. C.; Yang, F. (Phys. Rev. Lett., 2014)

(untitled) - Hahn, C.; de Loubens, G.; Naletov, V. V.; Ben Youssef, J.; Klein, O.; Viret, M. (EPL, 2014)

(untitled) - Shang, T.; Yang, H. L.; Zhan, Q. F.; Zuo, Z. H.; Xie, Y. L.; Liu, L. P.; Zhang, S. L.; Zhang, Y.; Li, H. H.; Wang, B. M.; Wu, Y. H.; Zhang, S.; et al. (J. Appl. Phys., 2016)

(untitled) - Lin, W.; Chen, K.; Zhang, S.; Chien, C. L. (Phys. Rev. Lett., 2016)

(untitled) - Moriyama, T.; Takei, S.; Nagata, M.; Yoshimura, Y.; Matsuzaki, N.; Terashima, T.; Tserkovnyak, Y.; Ono, T. (Appl. Phys. Lett., 2015)

(untitled) - Cramer, J.; Ritzmann, U.; Dong, B.-W.; Jaiswal, S.; Qiu, Z.; Saitoh, E.; Nowak, U.; Kläui, M. (J. Phys. D: Appl. Phys., 2018)

(untitled) - Hung, Y.-M.; Hahn, C.; Chang, H.; Wu, M.; Ohldag, H.; Kent, A. D. (AIP Adv., 2017)

(untitled) - Mangin, S.; Henry, Y.; Ravelosona, D.; Katine, J. A.; Fullerton, E. E. (Appl. Phys. Lett., 2009)

(untitled) - Zeng, Z.; Finocchio, G.; Jiang, H. (Nanoscale, 2013)

(untitled) - Smith, N.; Arnett, P. (Appl. Phys. Lett., 2001)

(untitled) - Sun, N. X.; Wang, S. X.; Silva, T. J.; Kos, A. B. (IEEE Trans. Magn., 2002)

(untitled) - McMichael, R. D.; Stiles, M. D.; Chen, P. J.; Egelhoff, W. F., Jr (J. Appl. Phys., 1998)

(untitled) - Rezende, S. M.; Lucena, M. A.; Azevedo, A.; de Aguiar, F. M.; Fermin, J. R.; Parkin, S. S. P. (J. Appl. Phys., 2003)

(untitled) - Kuanr, B. K.; Camley, R. E.; Celinski, Z. (J. Appl. Phys., 2003)

(untitled) - Yuan, S.; Kang, B.; Yu, L.; Cao, S.; Zhao, X. (J. Appl. Phys., 2009)

(untitled) - Layadi, A.; Artman, J. O. (J. Magn. Magn. Mater., 1990)

(untitled) - Heinrich, B.; Cochran, J. F.; Kowalewski, M.; Kirschner, J.; Celinski, Z.; Arrott, A. S.; Myrtle, K. (Phys. Rev. B, 1991)

(untitled) - Zhang, W.; Jungfleisch, M. B.; Jiang, W.; Pearson, J. E.; Hoffmann, A.; Freimuth, F.; Mokrousov, Y. (Phys. Rev. Lett., 2014)

(untitled) - Merodio, P.; Ghosh, A.; Lemonias, C.; Gautier, E.; Ebels, U.; Chshiev, M.; Béa, H.; Baltz, V.; Bailey, W. E. (Appl. Phys. Lett., 2014)

(untitled) - Rezende, S. M.; Rodríguez-Suárez, R. L.; Azevedo, A. (Phys. Rev. B, 2016)

(untitled) - Chen, K.; Lin, W.; Chien, C. L.; Zhang, S. (Phys. Rev. B, 2016)

(untitled) - Khymyn, R.; Lisenkov, I.; Tiberkevich, V. S.; Slavin, A. N.; Ivanov, B. A. (Phys. Rev. B, 2016)

(untitled) - Frangou, L.; Oyarzún, S.; Auffret, S.; Vila, L.; Gambarelli, S.; Baltz, V. (Phys. Rev. Lett., 2016)

(untitled) - Petti, D.; Albisetti, E.; Reichlová, H.; Gazquez, J.; Varela, M.; Molina-Ruiz, M.; Lopeandía, A. F.; Olejník, K.; Novák, V.; Fina, I.; Dkhil, B.; Hayakawa, J.; et al. (Appl. Phys. Lett., 2013)

(untitled) - Finegan, J. D.; Hoffman, R. W. (J. Appl. Phys., 1959)

(untitled) - Platt, C. L.; Minor, N. K.; Klemmer, T. J. (IEEE Trans. Magn., 2001)

(untitled) - Jhajhria, D.; Pandya, D. K.; Chaudhary, S. (RSC Adv., 2016)

(untitled) - Zhang, Y.; Fan, X.; Wang, W.; Kou, X.; Cao, R.; Chen, X.; Ni, C.; Pan, L.; Xiao, J. Q. (Appl. Phys. Lett., 2011)

(untitled) - Kittel, C. (Phys. Rev., 1948)

(untitled) - Lee, H.; Wen, L.; Pathak, M.; Janssen, P.; LeClair, P.; Alexander, C.; Mewes, C. K. A.; Mewes, T. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Devolder, T.; Ducrot, P.-H.; Adam, J.-P.; Barisic, I.; Vernier, N.; Kim, J.-V.; Ockert, B.; Ravelosona, D. (Appl. Phys. Lett., 2013)

(untitled) - Shaw, J. M.; Nembach, H. T.; Silva, T. J. (Phys. Rev. B, 2012)

(untitled) - Kamberský, V. (Czech. J. Phys., 1976)

(untitled) - Arias, R.; Mills, D. L. (Phys. Rev. B, 1999)

(untitled) - Lindner, J.; Barsukov, I.; Raeder, C.; Hassel, C.; Posth, O.; Meckenstock, R.; Landeros, P.; Mills, D. L. (Phys. Rev. B, 2009)

(untitled) - Lenz, K.; Wende, H.; Kuch, W.; Baberschke, K.; Nagy, K.; Jánossy, A. (Phys. Rev. B, 2006)

(untitled) - Ando, K. (Semicond. Sci. Technol., 2014)

(untitled) - Tserkovnyak, Y.; Brataas, A.; Bauer, G. E. W. (Phys. Rev. Lett., 2002)

(untitled) - Timopheev, A. A.; Pogorelov, Y. G.; Cardoso, S.; Freitas, P. P.; Kakazei, G. N.; Sobolev, N. A. (Phys. Rev. B, 2014)

(untitled) - McCord, J.; Kaltofen, R.; Schmidt, O. G.; Schultz, L. (Appl. Phys. Lett., 2008)

(untitled) - Hoffmann, H.; Fujii, T. (J. Magn. Magn. Mater., 1993)

(untitled) - Raju, M.; Chaudhary, S.; Pandya, D. K. (Eur. Phys. J. B, 2013)

(untitled) - Fulara, H.; Chaudhary, S.; Kashyap, S. C.; Pandya, D. K. (J. Appl. Phys., 2011)

(untitled) - Radu, F.; Etzkorn, M.; Schmitte, T.; Siebrecht, R.; Schreyer, A.; Westerholt, K.; Zabel, H. (J. Magn. Magn. Mater., 2002)

(untitled) - Prados, C.; Pina, E.; Hernando, A.; Montone, A. (J. Phys.: Condens. Matter, 2002)

(untitled) - Wang, Y. Y.; Song, C.; Cui, B.; Wang, G. Y.; Zeng, F.; Pan, F. (Phys. Rev. Lett., 2012)